Postemergence giant ragweed management as affected by soil and cover crop management, soybean planting time, and preemergence herbicide application - Guilherme Chudzik; Jose J. Nunes; Nicholas J. Arneson; Ryan P. DeWerff; Victor de Sousa Ferreira; Christopher Proctor; David E. Stoltenberg; Shawn Conley; Rodrigo Werle (Weed Technology, 2025)
Early soybean planting and cover crop adoption in the U.S. Midwest prompt investigation into the impact of these practices on weed community dynamics and best management practices. While previous research has explored different aspects of giant ragweed control, the specific integration among soil management practices, including cover crop adoption, soybean planting timing, and herbicide use, has not been thoroughly investigated. This study assessed the effects of soil management, soybean planting time, and preemergence (PRE) herbicide application on giant ragweed control and soybean yield in Wisconsin and Nebraska in 2022 and 2023. The study included a factorial arrangement of four soil management treatments (conventional tillage, no-till, and fall-planted cereal rye early terminated and terminated at planting [planting green]), two soybean planting times, and two PRE herbicide treatments (PRE and no PRE). POST herbicides were applied when ∼50% of giant ragweed plants within each treatment reached ∼10 cm in height. In Nebraska, cereal rye and tillage treatments without a PRE had at least 67% lower giant ragweed density than no-till at POST. In no-till, densities were at least 60% lower with PRE compared to no PRE. In Wisconsin, cereal rye did not reduce giant ragweed density at POST compared to no-till, likely due to relatively low biomass accumulation. In contrast, delayed soybean planting reduced giant ragweed density for most treatments but lowered soybean yield in no-till and planting-green treatments. The PRE herbicides had either no effect or positive effects on reducing giant ragweed density and increasing soybean yield. Overall, this study suggests that soil management and soybean planting timing are crucial for effective giant ragweed management in Wisconsin, where biotypes with a long emergence window during the spring and summer are present, while in Nebraska, soil management and soybean planting timing are less critical due to giant ragweed biotypes with an early and short emergence window in the spring.